Kajian Pustaka Karakteristik Fisiko-Kimia Jagung dari Nusa Tenggara Timur, dan Produk Turunan Tradisionalnya - Hyldegardis Naisali; Jatmiko Eko Witoyo; Panggulu Ahmad Ramadhani Utoro; Nelsy Dian Permatasari (AGRICA, 2023)
Corn is a carbohydrate-based food source in the East Nusa Tenggara (ENT) region and is the second staple food after rice. Corn has been a hereditary food ingredient in the ENT region from generation to generation with various local names. However, comprehensive literature studies discussing productivity, diversity, physicochemical characteristics, and traditional corn derivative products from ENT are still rare and limited. The purpose of writing this article is to review corn from ENT by emphasizing aspects of productivity, variety, physicochemical characteristics, and its traditional derivative products from various scientific sources. Literature studies showed that ENT's estimated corn production in 2021 is 750,166 tons from the three cultivated types: local, superior free-range, and hybrid. ENT's local corn has a variety of physical diversity, especially regarding grain color. Regarding chemical characteristics, ENT's local corn has a relatively complete nutritional and mineral content and is suitable for food. The local people of ENT have many traditional derivative products from corn with a total of >10 types of food, which are still sustainable from generation to generation and are processed simply with maintaining local wisdom. One famous traditional and ethnic food from ENT is "Jagung bose".